2022
DOI: 10.3892/etm.2022.11267
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac tromethamine alleviates IL‑1β‑induced chondrocyte injury by inhibiting COX‑2 expression

Abstract: Osteoarthritis (OA) is one of the most frequently diagnosed chronic diseases, and its prevalence is rising as life expectancy increases. The present study was designed to investigate the role of ketorolac tromethamine (KT) in OA by establishing an in vitro model in ATDC5 cells. The OA model was established through induction using 10 ng/ml IL-1β. KT was then used to treat the ATDC5 cells. An MTT assay was adopted to detect the viability of ATDC5 cells with or without IL-1β induction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Then, the NO in turn activates NF‐κB in a p38MAPK‐dependent manner, forming a positive feedback pathway that promotes apoptosis. Some research focus on reducing the production of ROS and NO, and so on, so as to inhibit IL‐1β‐induced apoptosis and inflammation progression 51–54 . However, it has been suggested that the effect of ROS on NF‐κB may be related to the duration of oxidative stress, so the sustained oxidative stress may instead inhibit NF‐κB activity 55 …”
Section: Introductionmentioning
confidence: 99%
“…Then, the NO in turn activates NF‐κB in a p38MAPK‐dependent manner, forming a positive feedback pathway that promotes apoptosis. Some research focus on reducing the production of ROS and NO, and so on, so as to inhibit IL‐1β‐induced apoptosis and inflammation progression 51–54 . However, it has been suggested that the effect of ROS on NF‐κB may be related to the duration of oxidative stress, so the sustained oxidative stress may instead inhibit NF‐κB activity 55 …”
Section: Introductionmentioning
confidence: 99%
“…5 Accumulating evidence suggests that an imbalance in the redox state, leading to oxidative stress in chondrocytes, is a key event that perturbs cartilage homeostasis during OA development. 6,7 Oxidative stress activates proinflammatory pathways 8 and can trigger an inflammatory response 9 and chondrocyte senescence, 10 thereby accelerating the degradation of cartilage ECM during OA pathogenesis. 11 Previous clinical studies have illustrated that oxidative stress, aging, and OA are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the progress of OA is associated with biological factors that disrupted the well‐being of chondrocytes and lead to an abnormal state 5 . Accumulating evidence suggests that an imbalance in the redox state, leading to oxidative stress in chondrocytes, is a key event that perturbs cartilage homeostasis during OA development 6,7 …”
Section: Introductionmentioning
confidence: 99%